Design, Formulation and Physicochemical Evaluation of Clotrimazole Chewing Gum: - Aslani, Abolfazl; Karbasizadeh Esfahani, Shekofeh (Galen Medical Journal, 2021)
Background: Oral candidiasis is widespread in the patients with immunodeficiency diseases. Chewing gums are considered as mobile drug delivery systems that affected locally or systemically via the oral cavity. This study aimed to develop and evaluate the formulation of clotrimazole chewing gums for patients having oral candidiasis. Materials and Methods: Fourteen formulations (F) were designed by Design-Expert, version 7. These formulations were different in the amount of gum bases and sweeteners. Gum bases of elvasti, 487, stick, and fruit C were heated up to 70°C. Clotrimazole powder, sugar, liquid glucose, glycerin, mannitol, xylitol, and maltitol as well as different flavoring agents were added to the gum bases at 40°C. Content and weight uniformity, organoleptic properties evaluation, releasing the active ingredient in the phosphate buffer pH, 6.8, and taste evaluation were analyzed by Latin square analysis. Also, the mechanical test was done on F13 and F14 formulations. Results: F14 was the best formulation in terms of organoleptic properties. This formulation had suitable size, hardness, softness, and lack of adhesion to teeth. F14 formulation released 89% and 97% of clotrimazole after 30 and 45 minutes, respectively. F14 content uniformity and weight variations were 9.83±0.086 mg and 1.14±0.09 g, respectively. F14 evaluation of mechanical properties showed Young’s modulus about 0.32 MPa, and yield point occurred at the stress of 0.599 MPa and strain of 4.1%. Conclusion: F14 was chosen according to its physicochemical and organoleptic properties. F14 had adequate hardness, lack of adhesion to the teeth, suitable size, and best drug release. Tutti Frutti was a proper flavoring agent for clotrimazole gum formulations.[GMJ.2021;10:e1084]